Covid-19 dan Studi Hukum: Bagaimana Mahasiswa Mencermati Peluang Publikasi di Tengah Pandemi? Covid-19 and Legal Studies: How Do Students Find Publication Opportunities in the Midst of a Pandemic? - Alkadri, Riska; Arifin, Ridwan; Holish, Amarru Muftie; Sari, Dewi Puspa; Resthiningsih, Lilies (Fakultas Hukum Universitas Negeri Semarang, 2021)
Student activists are one of the important pillars in nation building, not only in the student movement but also various breakthroughs for the progress of the nation, many are initiated by students. The development of the student activist movement requires that every student who is a member of various student institutions must not only have a critical and noble attitude, but also the ability to convey ideas and solve existing problems. A lot of bad stigma is attached to student activists, ranging from unsatisfactory levels of academic quality, not graduating on time, responsive and very reactive, harsh and with opposing views, to demonstrations colored by various violence. The stigma is only in a few cases, not all activists face such conditions, but this stigma seems to have been far attached. The development of student activists today demands that activists must also have three literacy skills: data literacy, human literacy, and technological literacy. However, based on the results of preliminary research on this activity, 90 percent of student activists from the Faculty of Law, UNNES agreed that activists must have a critical attitude and critical writing skills, but only about 10 percent of activists have taken it seriously (publishing ideas in various forms). . This activity is aimed at developing the critical skills of student activists through increasing publications in various media. This activity also aims to form a critical writing community for student activists and to present a concrete platform for channeling student activist ideas and solutions in written form that can be read by many people. This activity is carried out through a critical thinking approach in legal studies using the IRAC (Issue, Rule, Application, Conclusion) method which is commonly used in analyzing various cases in legal study thinking. This activity lasts for 8 (eight) months with several stages of activities involving partners (student activists) directly, as well as guides and managers.